LES PROBLEMES ENVIRONNEMENTAUX LIES A L’EMERGENCE DES ACTIVITES ECONOMIQUE EN MILIEU URBAIN : LE CAS DES ACTIVITES ARTISANALES DANS LA VILLE DE GRAND-BASSAM (CÔTE D’IVOIRE) - Jérôme, Aloko-N’Guessan; Rokia, Ouattara Yagnama (European Scientific Journal, ESJ, 2014)
The present article highlights the impact of the craft activities on the living environment in the city of Grand-Bassam. Characterized by their dimension (size) and the nature of their activity, the jobs by the craft sector are present in all the cities of Ivory Coast. This sector progresses in connection with the industry and the business (trade). The craft activities gather more than 800 active persons (our inquiries 2010) in the city of Grand-Bassam. However they are confronted with a problem of space. Of this fact craftsmen settle down everywhere in places not in compliance with their affectation (slums, on gutters, central reservations, below the lines of high voltages). As any economic activities, these generate impacts on the structure and the functioning of the space and the environment generally by the production of waste, the pollution of grounds and some water and air emissions. Today, historic city classified in the heritage (holdings) world of UNESCO and seaside, Grand-Bassam begins (affects) a process of development which at least must be long-lasting (sustainable). For that purpose, it is important to lay bare (to strip) the environmental problems (pollution of air, the ground, anarchy in the activity (occupation) of the space in touch with the practice of the craft (home-made) activities) to a consideration in this process. The major problem aroused by our study is the urban disorder observed in Grand-Bassam. As a consequence (accordingly), the objective of this article is to contribute to a better knowledge of the problems led (inferred) by the craft (home-made) activities in the city of Grand-Bassam. In other words, it will be a question of seeing why craftsmen(architects) are hurt in terms of distribution(casting) of spaces necessary for the practice of their job(business) and to show how these activities they establish(constitute) a danger in the environmental plan. The methodological approach adapted to lead this study took into account a bibliographical synthesis and fieldworks.